Inclusion and participation in the care of the preterm infant at neonatal unit: paternal perceptions - Eilane Carvalho; Patrícia Pereira de Oliveira Cercal Mafra; Lidiane Ferreira Schultz; Beatriz Schumacher; Luana Cláudia dos Passos Aires (Universidade Federal de Santa Maria, 2019)
Aim: to describe paternal perceptions about their participation and inclusion in the care of their preterm infants staying at a Neonatal Unit. Methods: a descriptive study with qualitative approach performed at a public maternity that is a reference hospital in Kangaroo Care, in the north of Santa Catarina, Brazil. The data were collected between June and August of 2017 through semi-structured interviews conducted with 11 fathers. Thematic analysis was used to analyze the data. Results: four categories were identified: to be a father of a preterm newborn and its impact on the family dynamic; the first paternal touch; becoming a father; the participation and inclusion of the father in the care of his hospitalized infant; the healthcare team actions to build a paternal leading role. Final considerations: the clinical condition of a preterm newborn and the interpersonal relationship with the healthcare team influence the paternal participation on the infant care. Therefore, it is necessary to promote paternal empowerment at the Neonatal Unit.